2013
DOI: 10.1186/1752-153x-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis and predictive modeling of polymorph descriptors

Abstract: BackgroundA computation approach based on integrating high throughput binding affinity comparison and binding descriptor classifications was utilized to establish the correlation among substrate properties and their affinity to Breast Cancer Resistant Protein (BCRP). The uptake rates of Mitoxantrone in the presence of various substrates were evaluated as an in vitro screening index for comparison of their binding affinity to BCRP.The effects of chemical properties of various chemotherapeutics, such as antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Also, contribution of PCA = 1–3 was very weak and may be irrelevant in all three QSAR models ( q 2 less than 0.30, r 2 less than 0.70). Also Fisher test, RMSE (root mean square error) and cross-validated-RMSE were calculated [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, contribution of PCA = 1–3 was very weak and may be irrelevant in all three QSAR models ( q 2 less than 0.30, r 2 less than 0.70). Also Fisher test, RMSE (root mean square error) and cross-validated-RMSE were calculated [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The predictive in silico models for BCRP substrates are somewhat limited. Briefly, Hazai et al 33 used support vector machines (SVM) to build a model to predict wild-type BCRP substrates; Zhong et al 34 employed genetic algorithmconjugate gradient-SVM (GA-CG-SVM) to discriminate substrates and nonsubstrates of BCRP; Sedykh et al 35 developed a set of QSAR models using SVM, random forests (RF), and k-nearest neighbors for identification of both substrates and inhibitors of 11 intestinal transporters, including BCRP; Erićet al 36 reported artificial neural network-(ANN) and SVM-based model ensembles for the prediction of transport and inhibition of Pgp and BCRP; Garg et al 37 reported an in silico SVM model for the classification of BCRP substrates and nonsubstrates, which can be used in tandem with a second one aimed to estimate the BBB permeability; Lee et al 38 developed a linear QSAR model to establish the relationship between specificity of BCRP substrates and their uptake rates by BCRP polymorphs. Finally, Ose et al 39 developed an SVM-based prediction system to predict substrates of 7 categories of drug transporters (among them, BCRP).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Advances in computer technology associated with the machine learning process have brought up the vital improvements in strategies for prevention and treatment of various diseases [ 4 , 5 ]. The computer based analysis techniques including artificial neural networks (ANN) and K-Nearest Neighbors Model (KNN) model made it possible to assess and predict the pharmaceutical parameters through the data mining methods [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%